An update on human astrocytes and their role in development and disease. Issue 4 (11th January 2020) - de Majo, Martina; Koontz, Mark; Rowitch, David; Ullian, Erik M.
Abstract: Human astrocytes provide trophic as well as structural support to the surrounding brain cells. Furthermore, they have been implicated in many physiological processes important for central nervous system function. Traditionally astrocytes have been considered to be a homogeneous class of cells, however, it has increasingly become more evident that astrocytes can have very different characteristics in different regions of the brain, or even within the same region. In this review we will discuss the features of human astrocytes, their heterogeneity, and their generation during neurodevelopment and the extraordinary progress that has been made to model these fascinating cells in vitro, mainly from induced pluripotent stem cells. Astrocytes' role in disease will also be discussed with a particular focus on their role in neurodegenerative disorders. As outlined here, astrocytes are important for the homeostasis of the central nervous system and understanding their regional specificity is a priority to elucidate the complexity of the human brain. MAIN POINTS: Human astrocytes are a heterogeneous class of cells characterized by regional and functional specificity. This is important to consider when developing preclinical astrocyte models. Human astrocytes play a pivotal role in neurodegeneration and need to be considered for novel therapies.